2012
DOI: 10.1007/s10965-011-9764-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanical behaviors of thermoplastic polyurethane thin film coated polyamide 6 fibers part II. A solution coating method

Abstract: Thermoplastic polyurethane thin film (TPU) coated PA6 fibers were prepared by dipping fibers into a TPU solution. The thickness of the thin film coating was 20 μ m. A series of polymer glycols which include polycarbonate, polyether and polyester were used for the preparation of the TPU. Both tensile strength and elongation at break of the TPU coated fibers increased although both magnitudes of the TPUs are much lower than for the original PA6 fibers. Also there was a significant improvement in the abrasion res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The FT-IR spectrum of PA6 was extensively studied in the literature, 67,68 and the absorption bands located at 834, 929, 960, 1029, and 1200 cm À1 suggest that the crystalline structure PA6 utilized in the present work is mainly constituted by the α-crystalline phase. 68,69 According to Yeh et al, 70 the band at 3293 cm À1 (a) can be associated with the N H stretching vibration of hydrogen-bonded N H groups in the crystalline phase.…”
Section: Microstructural and Chemical Propertiesmentioning
confidence: 99%
“…The FT-IR spectrum of PA6 was extensively studied in the literature, 67,68 and the absorption bands located at 834, 929, 960, 1029, and 1200 cm À1 suggest that the crystalline structure PA6 utilized in the present work is mainly constituted by the α-crystalline phase. 68,69 According to Yeh et al, 70 the band at 3293 cm À1 (a) can be associated with the N H stretching vibration of hydrogen-bonded N H groups in the crystalline phase.…”
Section: Microstructural and Chemical Propertiesmentioning
confidence: 99%
“…The blending of polyamide with TPU in injection moulding and compressed mould have been reported [28][29][30][31][32] but there is a paucity of reported work on fibre blending of PA6 and TPU. A study conducted by John and Furukawa [33] showed that PA6 fibres coated with TPU increase the tensile strength and the breaking elongation of the filaments.…”
Section: Introductionmentioning
confidence: 99%